Esophagogastric junction in systemic sclerosis: A study with the functional lumen imaging probe. Issue 8 (3rd May 2017) - Fynne, L.; Liao, D.; Aksglæde, K.; Lottrup, C.; Gregersen, H.; Bjerregaard, N. C.; Drewes, A. M.; Krogh, K.
Abstract: Background: Fibrosis and atrophy of esophageal smooth muscle cells cause gastro‐esophageal reflux and dysphagia in most patients with systemic sclerosis (SSc). Recent studies indicate that distensibility of the esophagogastric junction (EGJ), assessed with the Functional Lumen Imaging Probe (FLIP) may be a more sensitive and accurate measure of sphincter function than manometry. We aim to describe and compare distension parameters of the EGJ in a well‐characterized group of patients with SSc. Method: Twelve patients with SSc reporting reflux or dysphagia (11 women, median age 53 [range 35‐72], duration of disease: 1‐20 years) were investigated using distensibility testing of the EGJ. Patients were compared with 11 healthy volunteers (HV) (10 women, median age 53 [range 40‐68]). The pressure and minimum diameter along the EGJ during ramp distension were used for distensibility analysis. Key Results: Patients with SSc had significantly lower EGJ yield pressure (median: 4.0 mm Hg [Inter Quartile Range (IQR): 2.8‐7.7]) than HV (median: 6.2 mm Hg [IQR: 9.4‐26]) ( P =.007). Likewise, the pressure‐strain elastic modulus was lower in SSc patients (median 1.73 kPa [IQR: 1.16‐2.15]) than in HV (median 2.41 kPa [IQR: 1.85‐2.67]) ( P =.03), indicating the reduced resistance to distension in SSc patient. Conclusion & Inferences: Patients with SSc and symptoms of reflux and dysphagia have significantly reduced resistance to distension of the EGJ. Abstract : Assessing distensibility of EGJ is probably a more accurate measure of sphincter function. The FLIP holds great promise as a safe, easy‐to‐use, valid method for evaluating the EGJ.